Influence of Workload and Motivational Drivers on Nursing Care Behaviors: A Study at Pomalaa PHC - Nelce, Nelce; Narmi, Narmi; Dj. Gimpe, Susilawati; Aluddin, Aluddin; Umrana, Siti (PT. Nursing Genius Care, 2025)
Background: Caring is the essence of the implementation of nursing care. A nurse needs caring behavior in carrying out a comprehensive nursing care process, including for nurses at the Pomalaa Health Center. Several studies state that factors influence nurse caring behavior including workload and motivation. Purpose: The purpose of this study was to determine the relationship between workload and motivation in the caring behavior of nurses at the Pomalaa Health Center. Methods: his research is Quantitative Research with a Cross-sectional design carried out at the Pomalaa Health Center on April 21-28 2022 with a population of 45 Nurses at the Pomalaa Health Center. Sampling in this study uses a saturated sample technique. Results: The statistical test used to analyze the data is the Chi-square test. The test results on the workload variable obtained a p-value of 0.356 and the motivation variable p-value of 0.285. Conclusion: So it can be concluded that workload and motivation are not related to the caring behavior of nurses at the Pomalaa Health Center. It is suggested that future researchers look at other factors that can improve nurse caring behavior, especially in healthcare settings.